Confixal derivatives with initial bez- in Old Russian chronicles - Irina V. Erofeeva; Yulia K. Lukoyanova (Russian Language Studies)
The study considers confixal derivatives with the initial bez- in the original monuments of the Old Russian language, chronicles. The relevance of the study is in the importance of analyzing history of new word-formation types in the Russian language, which subsequently enriched the word-formation system with new models. Based on the research of Kazan linguists in the field of historical word formation, the authors prove the functional status of a unified two-element word-formation morpheme and its derivational potential in the history of the Russian language. The aim of the study is a comprehensive structural-semantic, functional, and conceptual analysis of confixal nominal forms with the initial bez- in the Old Russian language. The material of the study is the collection of the 11th-14th century chronicle texts in the historical corpus of Russian National Corpus. The aim was achieved with the following methods: historical, linguistic-textological, cognitive methods, the method of component analysis of semantics. As a result, we established that chronicle texts contain confixal derivatives with the initial bez- in three main word-formation types: (a) nouns with the meaning of action/ state with the second element -ie; (b) nouns with the meaning of person with the second element -ьnikъ, and (c) adjectives with the second element -ьnyi . The model with bez- implements a new principle of cognition, through dialectical negation of contradictions. In the initial written period, these forms had stylistic marking due to their complex morphemic structure, connection with Greek calques, and their Old Church Slavonic nature. Initially, nouns and adjectives with abstract semantics were used as productive bases for confixal derivatives. Therefore, the most common in Old Russian chronicles were derivatives with the initial bez- ( bezzakon’nyi ‘unlawful’, bezzakonie ‘lawlessness’, beshchislennyi ‘innumerable’, bezbozh’nyi ‘godless’) . The prospects of the research consist in examining the ways of further development of confixal derivatives with the initial bez- in the Old Russian period from the 15th to the 17th centuries both in terms of the new models and of expanding the word-formation base with names of a specific meaning.